All the world's a stage: transforming entrepreneurship education through design thinking. Issue 2 (13th February 2017) - Huq, Afreen; Gilbert, David
Abstract : Purpose: The purpose of this paper is to present an alternate approach to entrepreneurship pedagogy development through an iterative journey of co-ownership between students, industry partners and academic course teams to enhance student satisfaction and learning outcomes. Design/methodology/approach: Utilising design thinking, the pedagogy evolved over a three-year period (2013-2015) through iterative innovation in the delivery model and assessments, underpinned by notions of classroom community, constructivism, justice and equity, humour and role-play. Findings: The findings strongly validate the integration of notions of justice and equity, constructivism, humour and role-play as learning principles and delivery elements in entrepreneurship pedagogy to enhance student satisfaction and learning outcomes. A critical outcome of this design and delivery process is the reduction of barriers between students and teachers and the impact this has on creating a shared learning journey; a journey that in this case has resulted in meaningful outcomes for all involved. Research limitations/implications: Further research with longitudinal data is needed to validate the link between design-led entrepreneurship pedagogy and enhanced student learning outcomes as well as implications relating to graduate employability. In global settings, further data collection could also validate whether the findings are culturally neutral or culturally sensitive. Practical implications: Entrepreneurship educators will benefit from this pedagogical approach in seeking to meet the needs of business start-ups, intrapreneurial capacity-building and potentially, enhancement of graduate employability. The model also offers promise for other learning contexts. Originality/value: Design thinking has received scant attention in entrepreneurship pedagogy. This case study demonstrates how design thinking can enhance student satisfaction and learning outcomes by integrating notions of constructivism, justice and equity, humour and role-play in entrepreneurship curricula.